PKM-MGMP Matematika SMK Kabupaten Majene Pelatihan GeoGebra sebagai media pembelajaran matematika - Syamsuddin Syamsuddin; Arifin Tahir; Herlina Ahmad; Febryanti Febryanti; Ayu Rahayu (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Mathematics Teachers Conference (MGMP) Majene Regency, West Sulawesi Province is a professional forum whosescope includes mathematics subject teachers at public and private SMKs. The problem faced by partners in this case MGMPMathematics of Majene Regency Vocational Schools in general is the lack of knowledge and skills in using applications aslearning media especially GeoGebra applications. Based on the problems faced by partners, the purpose of the CommunityPartnership Program (PKM) activity is to provide training and mentoring for members of the MGMP Mathematics VocationalSchool Majene in using the GeoGebra application so that it can be used as a medium for learning mathematics. Phase I of thePKM implementation begins with the coordination and analysis of needs. Phase II preparation and validation of the GeoGebramodule. Phase III conducted a workshop on the application of GeoGebra on geometry and linear programs. Phase IV providesassistance to MGMP on the application of GeoGebra in the classroom. The instruments used in PKM activities consisted of two,namely (1) pretest and posttest in the form of performance tests and (2) questionnaires before and after PKM training andmentoring. The results of the analysis of the pretest, obtained an average value of MGMP performance tests in using theGeoGebra application that is equal to 56.17, while the average posttest value is 97.25. The results of the analysis of the initialquestionnaire obtained (1) the average value of the percentage of MGMP members who had heard of the GeoGebra applicationwas 25.71%. (2) the average value of the percentage of mathematics MGMP members who have used the GeoGebra applicationis 5.72%, while the analysis of the final questionnaire is obtained (1) the average value of the percentage of MGMP memberswho understand the use of the GeoGebra application is 100% (2) the average percentage of MGMP members who use theGeoGebra application in classroom learning is 100%. In general, the conclusion of the implementation of PKM is able toimprove the competence of MGMP Mathematics at Majene Regency Vocational School in implementing the GeoGebraapplication as a medium for learning mathematics.